Genetic diversity of biovar 3 and 4 of Ralstonia solanacearum causing bacterial wilt of tomato using BOX- PCR, RAPD and hrp gene sequences - SINGH, DINESH; SINHA, SHWETA; CHAUDHARY, GARIMA; YADAV, D K; MONDAL, K K (The Indian Journal of Agricultural Sciences, 2014)
Genetic diversity of Ralstonia solanacearum, causal agent of bacterial wilt of tomato was assessed by using three different molecular methods such as random amplified polymorphism DNA (RAPD), BOX-PCR and hrp (hypersensitive response and pathogenicity) gene sequence analysis technique. Twelve isolates of Ralstonia solanacearum belonging to biovar 3 (9 isolates) and 4 (3 isolates) were collected from Northern parts of India including Himachal Pradesh and Uttarakhand states from infected tomato plants. Out of 16 primers used in RAPD fingerprinting, four primers (OPA-2, OPA-11, OPC-5, OPE-7) showed monomorphic bands and remaining 12 primers exhibited polymorphic amplified products of both the biovars of R. solanacearum. The primer OPE-10 showed the highest level of genetic diversity among the isolates. Ten isolates of R. solanacearum were classified into two clusters at 20 per cent similarity coefficient and cluster 1 represented all isolates of biovar 3 (UTT-23, UTT-10, UTT-26, HPT11, UTT-9, UTT-32, HPC-3) and cluster 2 comprised the biovar 4 (UTT-22, HPT-3, UTT-24). BOX-PCR fingerprint of R. solanacearum clearly distinguished biovar 3 and 4 grouped into two distinct clusters at 40% similarity coefficient. Cluster 1 represented all isolates of R. solanacearum biovar 3 and cluster 2 comprised the biovar 4 isolates. The isolates of R. solanacearum have genetic diversity in hrpB gene, but it could not differentiate the isolates of biovar 3 and 4. However, the biovars 3 and 4 of R. solanacearum can be genetically distinguished by using BOX- PCR and specific primer of RAPD.